Relationship between Glycemic Levels and Treatment Outcome among Critically Ill Children admitted into Emergency Room in Enugu - Nwachinemere Davidson Uleanya; Elias Chikee Aniwada; Ikenna Chidiebele Nwokoye; Ikenna Kingsley Ndu; Christopher Bismarck Eke (BMC, 2017)
Abstract Background Critically ill children are those in need of immediate attention on arrival to an emergency room. The importance of glycemic level measurement as well as maintaining the patency of the airway, effective breathing and circulation cannot be overemphasied. It has been highlighted that the peak hyperglycemia and hypoglycemia predict poor prognosis, longer lengths of hospital stay and higher mortality. The study aims to assess the relationship between glycemic level and treatment outcomes as well as length of hospital stay. Methods Analytical cross sectional method was used to study critically ill children aged ≥1 month to ≤10 years admitted into the Children Emergency Room of Enugu State University Teaching Hospital, Enugu. Their admission blood glucose was done. Interviewer administered questionnaire was used to collect information including sociodemographics, duration of hospitalization and outcome of treatment. Data was analysed using SPSS version 20. Chi square, logistic regressions and Kruskal Wallis tests were done as appropriate. Results A total of 300 patients were recruited. One hundred and seventeen (39%) had hyperglycemia, 62 (20.7%) patients had hypoglycaemia and 121 (40.3%) had euglycemia. Two hundred and fifty two (84%) were discharged while 48 (16%) died. There was significant association between glycemic levels and treatment outcome (p = < 0.001). Among the 48 who died, 12 (25.0%) had euglycemia, 21 (43.75%) had hypoglycaemia while 15 (31.25%) had hyperglycemia. On multivariate analysis, there was statistically significant association between hypoglycaemia and mortality (p = < 0.001). Unadjusted, those children with hypoglycaemia at presentation were about 4.7 times (UOR = 0.21, 95% Cl: 0.08-0.38) and adjusted, about 5 times (AOR = 0.20, 95% CI: 0.09-0.47) less likely to survive compared with those with euglycemia. Although not statistically significant, those with hyperglycemia were about 1.3 times less likely to survive compared with euglycemic children, adjusted and unadjusted (UOR = 0.75, 95% Cl: 0.33-1.68). Conclusion While both hypo- and hyperglycemia are associated with mortality, hypoglycaemia had a greater effect than hyperglycemia. Glycemic levels significantly affects treatment outcome.